2020
DOI: 10.3892/mmr.2020.11520
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of circular RNA hsa_circ_0079787 in the peripheral blood of patients with axial spondyloarthritis

Abstract: axial spondyloarthritis (axSpa) is a chronic rheumatic disease involving the axial skeleton. recent evidence suggested that certain circular rnas (circrnas) have a crucial role in rheumatic diseases. However, the functions of circrnas in axSpa have remained largely elusive. The present study identified the utility of the circrna Homo sapiens (hsa)_circ_0079787 as a potential biomarker for axSpa. a total of 5 circrnas (hsa_circ_0002715, hsa_circ_0001947, hsa_circ_0079787, hsa_circ_0000367 and hsa_circ_0035197) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Luo et al demonstrated that low expression of hsa_circ_0079787 in peripheral blood of AS patients was negatively correlated with BASDAI, which was in concert with our data. 28 Collectively, the expression level of circRNA_0003307 was associated with disease activity. 29 CircRNA_0003307 activated the PI3K/AKT signaling pathway and affected the expression of the downstream inflammatory factors -TNF-α and TNFAIP2.…”
Section: Discussionmentioning
confidence: 99%
“…Luo et al demonstrated that low expression of hsa_circ_0079787 in peripheral blood of AS patients was negatively correlated with BASDAI, which was in concert with our data. 28 Collectively, the expression level of circRNA_0003307 was associated with disease activity. 29 CircRNA_0003307 activated the PI3K/AKT signaling pathway and affected the expression of the downstream inflammatory factors -TNF-α and TNFAIP2.…”
Section: Discussionmentioning
confidence: 99%
“…CircRNAs have been studied as potential diagnostic markers and therapeutic molecules in these diseases. In particular, ceRNA regulation has been found to play an important role in ankylosing spondylitis (AS), which is a subtype of JSpA [4]. Several studies have investigated the regulatory role of circRNAs in AS, highlighting the potential of these molecules as therapeutic targets for the disease [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs have been studied as potential diagnostic markers and therapeutic molecules in these diseases. In particular, ceRNA regulation has been found to play an important role in ankylosing spondylitis (AS), which is a subtype of JSpA [4]. Several studies have investigated the regulatory role of circRNAs in AS, highlighting the potential of these molecules as therapeutic targets for the disease [5][6][7][8][9].Integrative ceRNA regulatory networks, which incorporate data on circRNA, miRNA, and mRNA, can provide valuable insights into complex gene interactions and help identify potential biomarkers for the diagnosis and treatment of diseases such as JSpA.…”
mentioning
confidence: 99%
“…CircSIAE (hsa_circ_0000367) is a circRNA formed by reverse splitting of linear SIAE gene at the position chr11:124517260-124518071 on chromosome, consisting of 244 nucleotides. It is derived from a spline of SIAE mRNA associated with immune diseases and reported as a novel potential biomarker for emerging rheumatoid arthritis ( Luo et al., 2020 ; Zhou et al., 2020 ). In this study, we used cultured cell systems to study the effect of CVB3 infection on expression levels of circRNAs and to investigate potential downstream mechanisms of their involvement in viral processes.…”
Section: Introductionmentioning
confidence: 99%